Electrospray Ionization Mass Spectrometry of Non-Covalent Complexes Formed between N-Alkylimidazolium-Containing Zwitterionic Sulfonates and Protonated Bases. Issue 6 (December 2014) - Podjava, Anton; Kistkin, Svjatoslav; Ausekle, Elina; Priede, Elina; Mekss, Peteris; Zicmanis, Andris
This paper describes non-covalent complexes between zwitterionic 3-(1-alkyl-3 N -imidazolio)-propane-1-sulfonates and different amines. Electrospray ionization (ESI) mass spectrometry and collision-induced dissociation were used to measure the stability of such complexes in solution and in the gas phase. Generally, zwitterionic sulfonates formed more abundant complexes with protonated 5-methylcytosine (5-MCH) than with aliphatic amines. The results show that the association constants and half-dissociation threshold energies of these complexes nonlinearly depend on the alkyl chain length of the zwitterion. It is shown that the complexes with the lowest stability exist in acetonitrile solution or in the gas phase. The factors responsible for this complicated behavior are discussed. The structure of the complexes was investigated by quantum chemical calculations using molecular mechanics and density functional theory. Hydrogen bonding is proposed as the main type of interaction responsible for the stability of ion–zwitterion complexes. In summary, the information obtained in this study could be used for the development of the new derivatization reagents for some compounds containing amidinium groups, like 5-MCH, to increase selectivity of ESI-based methods.